Kinerja Angkutan Barang pada jalur Kereta Api di Sumatera Selatan - Nugroho, Cahyo Adi; Pribadi, Ocky Soelistyo; Soekirman, Atong; Hidayat, Masjarul; Mariana, Sandrina (Institut Transportasi dan Logistik Trisakti, 2024)
The study aims to determine the impact of the infrastructure and maintenance quality on On Time Performance to the company’s freight transportation railroad track performance in South Sumatra. The data of the research was collected from a population of 30 coal mining companies operating in the southern part of Sumatra. This research used Path Analysis as the data analysis techniques. The conclusion states that there is a significant positive direct and indirect influence of the infrastructure facilities and maintenance quality variable on the company’s goods transportation performance through OTP. In addition, the company’s freight transportation performance contributes directly to OTP. Based on the research findings, the company’s freight transportation performance can be maximized by improving the rolling stocks quality and maintenance through On Time Performance. The Path Analysis results show that the infrastructure maintenance directly contributes to OTP of 21.17 percent and contributes to the freight transportation performance of 17.04 percent.